Sauna, sweat and science II – do we sweat what we drink?. Issue 4 (4th July 2019) - Zech, Michael; Benesch, Marianne; Hepp, Johannes; Polifka, Steven; Glaser, Bruno
ABSTRACT: Inspired by a previous 'Sauna, sweat and science' study [Zech et al. Isot Environ Health Stud. 2015;51(3):439–447] and out of curiosity and enthusiasm for stable isotope and sauna research we aimed at answering the question 'do we sweat (isotopically) what we drink'? We, therefore, pulse-labelled five test persons in a sauna experiment with beverages that were 2 H-enriched at about +25, 600 ‰. Sweat samples were collected during six sauna rounds and the hydrogen isotope composition δ 2 Hsweat was determined using an isotope ratio mass spectrometer. Before pulse labelling, δ 2 Hsweat – reflecting by approximation body water – ranged from –32 to –22 ‰. This is ∼35 ‰ enriched compared to usual mid-European drinking water and can be explained with hydrogen-bearing food as well as with the respiratory loss of 2 H-depleted vapour. The absence of a clearly detectable 2 H pulse in sweat after pulse labelling and δ 2 Hsweat results of ≤+250 ‰ due to a fast 2 H equilibration with body water are moreover a clearly negative answer to our research question also in a short-term consideration. Given that the recovery of the tracer based on an isotope mass balance calculation is clearly below 100 %, we finally answer the question 'where did the rest of the tracer go?' GRAPHICAL ABSTRACT: